Structure activity relationships of human galactokinase inhibitors. Issue 3 (1st February 2015) - Liu, Li; Tang, Manshu; Walsh, Martin J.; Brimacombe, Kyle R.; Pragani, Rajan; Tanega, Cordelle; Rohde, Jason M.; Baker, Heather L.; Fernandez, Elizabeth; Blackman, Burchelle; Bougie, James M.; Leister, William H.; et al.
Graphical abstract